On gender norms, innovation and smallholder farming: Patterns and processes of change in rural Uganda - Rietveld, Anne (2024)
This thesis is about gender norms in the context of rural transformation and particularly focuses on innovation and smallholder farming. I posit that women and men in low- and middle-income countries, engage differently in farming, based on locally defined gender norms and roles which usually put men in advantaged positions. The first objective of this thesis is to increase understanding on processes of gender normative change and on how gender norms affect processes of (agricultural) innovation. The second objective is to adapt and design approaches and methodologies - to conduct gender research in the framework of AR4D - that have potential to contribute to gender equality, avoid reinforcing inequalities and that raise the critical consciousness of researchers and other stakeholders of AR4D. I adopt a systems’ approach and, across the different chapters, study gender as a system or apply a gender lens to study gender dimensions of farming systems. Four chapters are based on empirical research using mixed methods with an emphasis on qualitative research methodologies and one chapter describes the design of a new method that supports gender-responsive scaling of agricultural innovations. My empirical research is situated in the rural areas of Central and Western Uganda.